Exploitation of bacterial N-linked glycosylation to develop a novel recombinant glycoconjugate vaccine against Francisella tularensis. Issue 5 (May 2013) - Cuccui, Jon; Thomas, Rebecca M.; Moule, Madeleine G.; D'Elia, Riccardo V.; Laws, Thomas R.; Mills, Dominic C.; Williamson, Diane; Atkins, Timothy P.; Prior, Joann L.; Wren, Brendan W.
Abstract : Glycoconjugate-based vaccines have proved to be effective at producing long-lasting protection against numerous pathogens. Here, we describe the application of bacterial protein glycan coupling technology (PGCT) to generate a novel recombinant glycoconjugate vaccine . We demonstrate the conjugation of the Francisella tularensis O-antigen to the Pseudomonas aeruginosa carrier protein exotoxin A using the Campylobacter jejuni PglB oligosaccharyltransferase . The resultant recombinant F. tularensis glycoconjugate vaccine is expressed in Escherichia coli where yields of 3 mg l −1 of culture were routinely produced in a single-step purification process. Vaccination of BALB/c mice with the purified glycoconjugate boosted IgG levels and significantly increased the time to death upon subsequent challenge with F. tularensis subsp. holarctica . PGCT allows different polysaccharide and protein combinations to be produced recombinantly and could be easily applicable for the production of diverse glycoconjugate vaccines.